2013
DOI: 10.1111/tbed.12152
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Recent Serotype O Foot-and-Mouth Disease Viruses from Livestock in Kenya: Evidence of Four Independently Evolving Lineages

Abstract: Citation (APA):Wekesa, S. N., Muwanika, V. B., Siegismund, H. R., Sangula, A. K., Namatovu, A., Dhikusooka, M. T., ... Belsham, G. (2015 from Eastern Africa, it was apparent that the outbreaks were caused by viruses from three different lineages of topotype EA-2 and a fourth virus strain belonging to topotype EA-4. The topotypes EA-1 and EA-3 were not detected from these outbreaks. Implications of these results for FMD control in Eastern Africa are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…No other viruses isolated after that period have been observed to belong to these genotypes suggesting that they may be extinct in the country. This observation, however, does not rule out their existence elsewhere in the region (as is also apparent from the lack of reports on G-I referred to above) and due to the extensive transboundary movement of animals and transmission of viruses as recently reported for serotype O FMDV by Balinda et al, (2010a) and Wekesa et al, (2013).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…No other viruses isolated after that period have been observed to belong to these genotypes suggesting that they may be extinct in the country. This observation, however, does not rule out their existence elsewhere in the region (as is also apparent from the lack of reports on G-I referred to above) and due to the extensive transboundary movement of animals and transmission of viruses as recently reported for serotype O FMDV by Balinda et al, (2010a) and Wekesa et al, (2013).…”
Section: Discussionmentioning
confidence: 85%
“…The genetic diversities of other previously circulating serotypes in Kenya including serotypes O Wekesa et al, 2013), C (Sangula et al, 2011), SAT 1 and SAT 2 have been extensively studied recently but not serotype A.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, these viruses belong to two different lineages within the EA‐2 topotype based on a cut‐off of >7.5% nucleotide difference for separating lineages and <15% difference among topotypes in the VP1 coding region of FMDV RNA (Vosloo et al., ; Samuel and Knowles, ). The U04/11 and U19/11 viruses were each very closely related to a FMDV isolate (K251/2010) from Kwanza, Western Kenya (Wekesa et al., ) with nucleotide identity of 634/639 (99%), while both the U07/11 and U24/11 isolates were closely related to the U18/06 virus from Mpigi district, Uganda with nucleotide identities of 96%.…”
Section: Resultsmentioning
confidence: 92%
“…() using reactions of 50 μl volume containing: 25.1 μl of water, 5 μl 10 × AmpliTaq Gold buffer, 4 μl MgCl 2 (25 m m ), 0.4 μl dNTPs (2.5 m m each), 0.5 μl of Amplitaq Gold ® DNA polymerase (Applied Biosystems, Life Technologies), 5 μl of template cDNA and 5 μl of the forward (11‐FPN 29: 5′–3′ GCIGCIGACTACGCITACACYGC, where I = inosine and Y = C or T) and reverse (11‐FPN 28: 5′–3′ GGGCCCAGGGTTGGACTC) primers, both at a concentration of 5 pmol/μl as used by Wekesa et al. ().…”
Section: Methodsmentioning
confidence: 99%
“…These descriptions and subsequent risk factor studies have focussed primarily on farm-to-farm level transmission, since control policies have emphasised preventing the virus moving to non-infected holdings (Wilesmith et al, 2003;Ellis-Iversen et al, 2011;Muroga et al, 2013). In endemic countries like those in subSaharan Africa, studies of FMD have tended to focus on genetic sequencing with phylogenetic tree construction (Sahle et al, 2007;Balinda et al, 2010;Sangula et al, 2010b;Wekesa et al, 2013), ecological studies on spatiotemporal distribution of reported outbreaks (Ayelet et al, 2012;Allepuz et al, 2013), seroprevalence (Bayissa et al, 2011;Kibore et al, 2013), and the role of wildlife (Caron et al, 2013).…”
Section: Introductionmentioning
confidence: 99%